Modulation of miR-145 in a mouse model of multiple sclerosis: A promising approach to attenuate inflammation and degeneration - Monique Marylin Alves de Almeida; Samantha F. Kornfeld; Yves De Repentigny; Majd Al-Aarg; Ibrahim Ghani; Sarah E. Cummings; Emma R. Sutton; Rebecca Yaworski; Kelsea S. McKay; Sabrina Gagnon; Ariane Beauvais; Rashmi Kothary (Neurobiology of Disease)
Multiple sclerosis (MS) is a progressive inflammatory disease of the central nervous system (CNS) marked by myelin loss, which impairs nerve function. Current therapies fail to halt disease progression or prevent myelin and axonal degeneration. In this study, we explored the impact of miR-145 loss in a murine model of experimental autoimmune encephalomyelitis (EAE), which mimics MS pathology. Loss of miR-145 reduced clinical severity and significantly decreased immune cell infiltration in the lumbar spinal cord during both the onset and chronic stages of the disease. Additionally, miR-145 loss altered the expression of key inflammatory genes and modulated astrocytic activity throughout EAE. Of significant interest, acute treatment with an antisense oligonucleotide (ASO) targeting miR-145 decreased miR-145 levels and led to reduced disease severity, decreased immune cell infiltration, and an increase in regulatory T cells in EAE mice. Moreover, miR-145 deficiency mitigated axon and myelin degeneration. Our findings suggest that ASOs targeting miR-145 may offer a promising therapeutic strategy, addressing both inflammatory and degenerative components of MS.